Intention to Leave Among Frontline Homeless Services Workers in the U.S.: A Mixed Methods Analysis - Aykanian, Amanda; Frank, Jennifer M.; Eyrich-Garg, Karin M. (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
Studies in the United States (U.S.), Canada, Australia, the United Kingdom (UK), and across Europe have highlighted similar workforce challenges in the homeless services sector and concerns about their impact on staff turnover. However, research has not sufficiently studied what contributes to turnover in the sector. The current study used quantitative and qualitative data from a national survey of frontline homeless services workers in the U.S. to answer questions about workers’ intention to leave their current job and reasons for intending to leave. Quantitative findings show that 43% of frontline workers reported an intention to leave. Factors associated with a greater likelihood of intending to leave included holding at least a master’s degree and experiencing higher burnout. Factors associated with a lower likelihood of intention to leave included Hispanic race and higher scores on three domains of job satisfaction: pay, promotion opportunities, and the nature of the work. The qualitative data confirmed the importance of burnout, inadequate pay, and the challenging nature of the work in contributing to an intention to leave. The qualitative findings also shed light on additional drivers of intention to leave, including personal reasons (e.g., caretaking responsibilities), problems with the organization, and lacking the resources needed to help clients. Opportunities to increase pay and promotion opportunities, prevent and mitigate burnout, and strengthen organizations are offered. Suggested directions for future research are also provided, including evaluating the impact of employee retention strategies (e.g., pay increases, well-being supports, and organization-level interventions).